Effect of Panchagavya and GA3 on Germination and Seedling Growth in Cashew (Anacardium occidentale L.) - Singh, L S; Pariari, A; Shukla, Gopal (Journal of Horticultural Sciences, 2015)
An experiment consisting of three sowing periods (March-May, June-August and September-November) and seven pre-sowing treatments was undertaken to study the effect of these factors on seed germination and initial seedling growth in cashew. Seeds sowing during June - August gave significantly better germination and initial seedling growth. However, maximum germination percentage, maximal seedling growth and minimum days to germination were observed with GA3 200ppm during all three sowing periods compared to that in other treatments. As for panchagavya, @ 10% and 20%, was found to be beneficial in treated seeds. All the growth parameters studied were also superior with GA3 application,excepting root growth. Best root growth was recorded with panchagavya at 20%.
Keywords: Cashew; Anacardium occidentale L.; GA3; Germination; Growth; Panchagavya